The Coaching Habit Say less, ask more and change the way you lead forever - Stanier, Michael (Toronto Page Two, 2016)
In Michael Bungay Stanier's The Coaching Habit, coaching becomes a regular, informal part of your day so managers and their teams can work less hard and have more impact.
Keywords: Coaching